Socio-Economic Determinants of Migration Processes and the Mechanism of Their Regulation - Kyfyak, Viktoria; Kindzerskyy, Vitaliy; Antochova, Irina (Review of Economics and Finance., 2022)
The modern paradigm of socio-economic system development is determined by fluctuation changes and the transformation of integration in the migration processes regulation. In conditions of fluctuating transformations and social challenges, the analysis and migration processes regulation should be considered as a key issue of global social activity, and as the establishment of a strategic foundation for their development. The search for an effective analyzing method of the migration processes determinants and mechanisms for their regulation, which would com-bine global and regional mechanisms for regulating migration processes, is relevant. The aim of the study is to assess the socio-economic determinants of migration processes and to form a mechanism for their regulation. The object of research is the heterarchical structure of socio-economic relations that have developed in the process of regulating migration processes. The research is based on a systematic approach, which is used to define the determinants of mi-gration processes in their relationship and interaction and to form a structure for regulating migration processes. An integrated methodological approach was used for assessment and verifying the influence of various indicators of possible impact on migration, i.e., for evaluation by a system of indicators, which provided a high level of validity. The bootstrap method was used to build a model of migration processes determinants. This method is a means of constructing an empirical distribution and definition of the main determinants of migration processes. The method of structuring is used in the formation of the model of the hierarchical structure of migration processes regulation.
Keywords: Migration Processes; Socio-Economic Determinants; Bootstrap Method; Heterarchical Structure of Regulation; Institutional Agreements.